The electric state - Stålenhag, Simon (Skybound Books, 2018)
"A teen girl and her robot embark on a cross-country mission in this illustrated science fiction story, perfect for fans of Ready Player One and Black Mirror. In late 1997, a runaway teenager and her small yellow toy robot travel west through a strange American landscape where the ruins of gigantic battle drones litter the countryside, along with the discarded trash of a high-tech consumerist society addicted to a virtual-reality system. As they approach the edge of the continent, the world outside the car window seems to unravel at an ever faster pace, as if somewhere beyond the horizon, the hollow core of civilization has finally caved in"--